Trends of Patients' Preferences in the Management of First and Early Second Trimester Pregnancy Loss Towards the Choice of Medical or Surgical Termination of Pregnancy in a Tertiary Care Center in Oman - Al-Dughaishi, Tamima; Hamed Al-Jabri, Mussab; Al-Haddabi, Amjad; Gowri, Vaidyanathan (Journal of Reproduction & Infertility, 2019)
Background: This study aimed to find out the patients preference towards the managementof pregnancy loss to either Misoprostol or dilatation and evacuation or curettage (D&C) in two different study periods. Methods: Retrospective chart review study included a total of 411 patients. The first study period was January to December 2010 and the second study period was January to December 2014. All patients were managed in Sultan Qaboos University Hospital of Oman. Results: Misoprostol was more preferable than dilatation and curettage D&C in both 2010 and 2014, with percentages of 79.30% and 69.57%, respectively. There was a slight increase in the preference toward D&C in 2014. There was a slight increase in the preference toward D&C with older age group as well as in patients with history of miscarriages. Conclusion: In comparison between 2010 and 2014 data, there was no significant change in patients’ preference. There was a slight increase in the preference toward D&C in the older age group and in patients with previous history of abortion in both years.